Experimental Study on the Effect of Hydraulic Cavitation on the Physical and Chemical Properties of Water - HAN Gui-hua; JU Peng-bo; ZHAO Zhiwei; LI Da-wei; ZHAO Meng-shi; PEI-Yu; YAO Hong-bin; YAO Li-ming (Journal of Harbin University of Science and Technology)
The hydrodynamic cavitation process is accompanied by the initiation, growth, collapse and instantaneous high temperature and high pressure of the bubble collapse. The effect of this cavitation effect on the cavitation medium itself has been lacking in research. In this paper, singlehole and fivehole platetype cavities are used as experimental devices to study the influence of hydraulic cavitation effects on the physicochemical properties of water. First, under the same cavitation time and measurement temperature, We adjust the different inlet pressures of the cavitation device (0.3MPa,0.5MPa,0.7MPa,1MPa), and conduct conductivity and dissolution of the cavitation water sample in the orifice cavitation device, oxygen, pH test, the three properties of the water sample with the inlet pressure and time curve. The experimental results show that as the inlet pressure increases, the conductivity first gradually increases and then gradually decreases: dissolved oxygen first gradually decreases and then gradually rises; pH is less affected by the effect of hydraulic cavitation, and there is no obvious change rule overall.